THE HOLISTIC LEARNING MODEL OF BUSINESS ETHICS TO DEVELOP SPIRITUAL WELL-BEING - Yuniarwati, Yuniarwati; Ardana, I Cenik; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2024)
The purpose of this study is to investigate the impact of the holistic learning model of Business Ethics on the students’SWB. Two business ethics classes are randomly chosen as sample from all business ethics classes of Management Study Program, Tarumanagara University, Jakarta. The study uses a quasi-experimental design “pre-test-post-test design with one group”, in which the learning model is the independent variable and the students’ SWB is the dependent variable. The testing of hypothesis uses the SWB’s score mean differences of a paired sample t-test. The results of this study show that the holistic learning model of Business Ethics gives a significant impact on the quality improvement of the students’ SWB, both overall and on all four dimensions of SWB: communal, personal, transcendental, and environmental. Three dimensions: communal, transcendental, and environmental influence at a significant level of 5%; and one dimension (personal) has an effect on a significance level of 10%.